2016
DOI: 10.1109/tsc.2015.2456889
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Virtual Chunks: On Supporting Efficient Accesses to Compressed Scientific Data

Abstract: Data compression could ameliorate the I/O pressure of data-intensive scientific applications. Unfortunately, the conventional wisdom of naively applying data compression to the file or block brings the dilemma between efficient random accesses and high compression ratios. File-level compression barely supports efficient random accesses to the compressed data: any retrieval request need trigger the decompression from the beginning of the compressed file. Block-level compression provides flexible random accesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Possible future work could include HFE-based ring routing in WSNs, HFE-based heterogeneous clustering supporting sink mobility, HFE based on Cognitive Radio Sensor Networks (CRSN) etc. In addition to this, the proposed scheme can be applied to ring routing [49], big data systems [50], data compression [51] and blockchain technology [52] in terms of reliable data fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Possible future work could include HFE-based ring routing in WSNs, HFE-based heterogeneous clustering supporting sink mobility, HFE based on Cognitive Radio Sensor Networks (CRSN) etc. In addition to this, the proposed scheme can be applied to ring routing [49], big data systems [50], data compression [51] and blockchain technology [52] in terms of reliable data fusion.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the proposed data fusion algorithm could improve the reliability of data compared to the state-of-the-art. In the future, we plan to integrate the proposed data fusion algorithm into other system research areas, such as big data systems [ 28 ], key-value stores [ 29 ], data compression [ 30 ], and blockchains [ 31 ].…”
Section: Discussionmentioning
confidence: 99%